2005
DOI: 10.1007/s00467-005-1883-z
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis in children

Abstract: A metabolic etiology is the most common cause for pediatric kidney stones. Appropriate evaluation of affected children should include assessment of stone type, if available, and assessment of predisposing factors in all cases. This review discusses the metabolic disorders that lead to nephrolithiasis with respect to the development of calcium, uric acid, struvite, and cystine stones. Environmental and hereditary factors are summarized to provide a guide in the evaluation of pediatric stone formers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 39 publications
5
55
1
4
Order By: Relevance
“…6 This study found that 38.5% of the infants with urolithiasis have some metabolic abnormality, as follows: 20% had hypercalciuria, 9.6% had hypocitraturia, 6.7% had hyperuricosuria, and 1.9% had hyperoxaluria. By way of comparison, in infantile cases, hypercalciuria was detected in 48% in Baştug 's study, 1 25% in Gü ven's study, 2 and 30.8% in Alpay's study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…6 This study found that 38.5% of the infants with urolithiasis have some metabolic abnormality, as follows: 20% had hypercalciuria, 9.6% had hypocitraturia, 6.7% had hyperuricosuria, and 1.9% had hyperoxaluria. By way of comparison, in infantile cases, hypercalciuria was detected in 48% in Baştug 's study, 1 25% in Gü ven's study, 2 and 30.8% in Alpay's study.…”
Section: Discussionmentioning
confidence: 73%
“…Factors leading to urolithiasis include metabolic abnormalities, genetics, nutrition, environment, and specific medicines. 6,7 Hypercalciuria is the most common metabolic abnormality. 2,8 Infantile urolithiasis represents 9-23% of all pediatric cases; approximately, 60% of infants have family history of stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…15,20,24,52,53 Ancak üriner sistemin yapısal anomalileri olan hastalarda metabolik bozukluklar da (hiperokzalüri, hiperkalsiüri, hipositratüri) olabilir ve çalışmalarda bu çocukla-rın %66-80'inde metabolik anomaliler saptanmış-tır. 12,13,54,55 Bu nedenle yapısal anomalileri olan çocuklarda da tam bir metabolik değerlendirme yapılmalıdır.…”
Section: üRi̇ner Si̇stemi̇n Yapisal Anomali̇leri̇unclassified
“…Bazı çalışmalarda her iki cinste eşit oranda görüldüğü bildirilirken, bazılarında ise erkeklerde daha fazla görüldüğü belirtilmektedir. 6 Irk ve coğ-rafya, çocuklardaki taş olgularında prevalans ve etiyolojide önemlidir. Örneğin; Güneydoğu Asya, Orta Doğu, Hindistan ve Pakistan gibi dünyanın bazı bölgelerinde ürolitiyaz endemik iken, Afrikalı çocuklarda ürolitiyaza nadiren rastlanmaktadır.…”
unclassified
“…Infectious stones (struvite stones -magnesium ammonium phosphate), previously accounted for a significant proportion of stones among European children 10 . However, as a result of improvements in the diagnosis and treatment of UTI in children over the past decades, the aetiology of renal stones in children has shifted from predominantly infectious to metabolic causes 11 with a predominance of calcium based stones 12 .…”
Section: Pathophysiology Of Stone Formationmentioning
confidence: 99%